2016
DOI: 10.4103/0970-2113.177438
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of chronic obstructive pulmonary disease patients: Results from a community based cross-sectional study in Aligarh, Uttar Pradesh, India

Abstract: Background:Chronic obstructive pulmonary disease (COPD) is characterized by airflow limitation that is not fully reversible. It is an incurable disease with improvement in quality of life (QOL) as a major focus area for management. This study assesses the QOL of COPD patients and the factors affecting it.Materials and Methods:All 124 patients diagnosed with COPD in a larger cross-sectional study to determine the prevalence of COPD were assessed for their QOL using St. George's respiratory questionnaire for COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
43
7
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 34 publications
15
43
7
4
Order By: Relevance
“…Other studies also reported no correlation between age and QOL while some have reported worsening of SGRQ scores with increasing age. 3,7,8 Sex did not impact QOL in significant manner in the present study. Some studies have reported that females have poor QOL as compared to males.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Other studies also reported no correlation between age and QOL while some have reported worsening of SGRQ scores with increasing age. 3,7,8 Sex did not impact QOL in significant manner in the present study. Some studies have reported that females have poor QOL as compared to males.…”
Section: Discussioncontrasting
confidence: 50%
“…Ahmed et al also showed impairment of QOL across all domains. 3 Symptom domain was found to be most affected while impact domain was the least affected. Negi et al also found marked impairment of HRQL.…”
Section: Discussionmentioning
confidence: 86%
“…Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide and is associated with poor quality of life (QoL) and a significant burden on healthcare resources [1,2]. Current population-level strategies to reduce the burden of COPD have largely focused on smoking cessation, the most significant modifiable risk factor for the development and progression of COPD [3].…”
Section: Introductionmentioning
confidence: 99%
“…[12] A cross-sectional study was conducted in a larger community by Malik shanawaz Ahmad et al shows that 10.2% have unwell quality of life. [3] A Study conducted by Mcnicholas et al on prevalence and impact of quality of life and quality of sleep in COPD patients found that 61%…”
Section: Prevalence Of Sleep Disturbance In Copd Patientsmentioning
confidence: 99%
“…[2] According to world health organization, COPD would be the third largest common source of cessation and impairment by 2030 in the world, from its existent fifth position. [3] The Global Initiative for Obstructive Lung Disease (GOLD) characterizes COPD [4] Sleep disorder is the third most common manifestation allied with COPD. [5] The prevalence of midnight symptoms and significant disorders is 75% with the COPD patients.…”
Section: Introductionmentioning
confidence: 99%